Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2020)
A dataset containing 1062 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Actinastrum Lagerheim, 1882" ] } The dataset includes 1062 records from 66 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0070238-200613084148143/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences